Creation of a Neo-Vagina in Mullerian Agenesis by Three Different Method and Literature Review - Aslan, Melike; Pala, Şehmus; Mirzaoğlu, Miyase; Atilgan, Remzi; Yavuzkır, Şeyda (My University, 2024)
Mullerian agenesis is a rare malformation and there are several non surgical and surgical techniques to treat. We aimed to present 3 different neovagina creation techniques that we applied to women with Mullerian agenesis who applied to our clinic and to review the literature. Twelve patients diagnosed with Mullerian agenesis and underwent neovagina creation procedure between 2016 and 2021 were included in the study. One of the neovagina techniques, the McIndoe procedure was applied to 2 patients, the Frank method to 4 patients, and the Laparoscopic Davydov vaginoplasty to 6 patients. Pre- and postoperative vaginal lengths, time of sexual intercourse, pain during intercourse, and operation complications were recorded. The 12 patients who underwent neovagina reconstruction were aged 18–31 years (mean 24.4 years). Physiologic vaginal length was achieved in all patients (mean length 7.9 cm). Vaginal hair growth was observed in both patients who underwent McIndoe. In a patient who underwent Davydov, 1 unit of erythrocyte suspension was administered owing to intraoperative bleeding during vesicorectal dissection. Neovagina techniques applied to optimize sexual life in women with Mullerian agenesis should be individualized according to the patient.
Keywords: Davydov; Mullerian Agenesis; Neovagina; Frank; Mc-Indoe